Towards an improvement in the spectral description of central stars of planetary nebulae - Weidmann, Walter Alfredo (2018)
Context. There are more than 3000 known Galactic planetary nebulae, but only 492 central stars of Galactic planetary nebulae (CSPN) have known spectral types. It is vital to increase this number in order to have reliable statistics, which will lead to an increase of our understanding of these amazing objects. Aims. We aim to contribute to the knowledge of central stars of planetary nebulae and stellar evolution. Methods. This observational study is based on Gemini Multi-Object Spectrographs (GMOS) and with the Intermediate Dispersion Spectrograph (IDS) at the Isaac Newton Telescope spectra of 78 CSPN. The objects were selected because they did not have any previous classification, or the present classification is ambiguous. These new high quality spectra allowed us to identify the key stellar lines for determining spectral classification in the Morgan-Keenan (MK) system. Results. We have acquired optical spectra of a large sample of CSPN. From the observed targets, 50 are classified here for the first time while for 28 the existing classifications have been improved. In seven objects we have identified a P-Cygni profile at the He I lines. Six of these CSPN are late O-Type. The vast majority of the stars in the sample exhibit an absorption-Type spectrum, and in one case we have found wide emission lines typical of [WR] stars. We give a complementary, and preliminary, classification criterion to obtain the sub-Type of the O(H)-Type CSPN. Finally, we give a more realistic value of the proportion of CSPN that are rich or poor in hydrogen.